Near-Infrared Spectroscopy Detection of Off-Flavor Compounds in Tench (Tinca tinca) After Depuration in Clean Water - Daniel Martín-Vertedor; Juan Carlos Ramírez-López; Ricardo S. Aleman; Elisabet Martín-Tornero; Ismael Montero-Fernández (Foods)
Tench (Tinca tinca) is a warm-temperate, freshwater benthic fish with often unpleasant odors and flavors which result from its natural habitat. These characteristics may deter consumers; therefore, their removal would enhance the fish’s palatability and market appeal. Thus, tench were grown in an aquaculture center and subjected to a clean water depuration system in which six sampling points were carried out at 0 h, 12 h, 24 h, 48 h, 72 h, and 96 h. An analysis was conducted using gas chromatography–mass spectrometry and near-infrared spectroscopy (NIRS), revealing acid derivatives as the predominant families of volatile organic compounds (VOCs). The main off-flavor VOCs were 3,5,5-trimethyl-1-hexene, dimethyl-8-hydronaphtalen, 1-octen-3-ol, diethyl phthalate, 2-methylisoborneol, and a-isomethylionone. Maximum concentrations were observed at 0 h, exceeding 300 μg/g for diethyl phthalate and being less than 55 μg/g for the remaining VOCs. The content progressively decreased from that point on. The spectra obtained by NIRS highlighted differences between the cleaning depuration treatments, exhibiting discrimination among the samples studied (PC1 = 77.8%; PC2 = 11.3%). Finally, dimethyl-8-hydronaphtalen and 2-methylisoborneol were linearly correlated with NIRS data, with <semantics><msubsup>RCV2</msubsup><mtext> </mtext></semantics> values of 0.94 and 0.96, respectively, and RMSECV values of 1.00 and 3.62 μg/g, respectively. Therefore, a clean water depuration system is appropriate to obtain fish with fewer off-flavor characteristics. Moreover, NIRS represents an accurate, inexpensive, and non-destructive technique to determine the optimal time for the water depuration of fish.